Women's Murder Club : 11th Hour - Patterson, James 1947-; Paetro, Maxine; LaVoy, January (New York Hachette Audio, 2012)
Investigating the murder of a millionaire who was killed with a weapon linked to the deaths of four San Francisco criminals, pregnant detective Lindsay Boxer is horrified to realize that the killer could be among her closest friends.
Unabridged.
Compact discs.
Read by January LaVoy.
Keywords: Women detectives -- Fiction -- California; Murder -- Fiction -- Investigation; Police corruption -- Fiction; Man-woman relationships -- Fiction; San Francisco (Calif.) -- Fiction; Suspense fiction; Mystery fiction; Audiobooks